2017
DOI: 10.4093/dmj.2017.41.4.296
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Mortality in People with Type 2 Diabetes Mellitus, 2003 to 2013: A Nationwide Population-Based Cohort Study

Abstract: BackgroundPrevious reports have demonstrated a bidirectional relationship between depression and diabetes mellitus (DM), accentuating a need for more intensive depression screening in DM patients. There is a relative paucity of data on the mortality of depressed DM patients in Korea.MethodsRetrospective data from January 2003 to December 2013 were collected for adult type 2 diabetes mellitus (T2DM) patients older than 30 years using the National Health Information database maintained by the Korean National Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Previously, the prevalence of depression in patients with T2DM in Korea has been reported as high as 22.6% to 28.8% [ 18 19 ]. In the analysis using the NHIS DB, depression in T2DM was defined as both T2DM and depression (ICD-10 code of F320-349) with at least one prescription for antidepressants ( Table 1 ) [ 20 ].…”
Section: Depression In T2dmmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, the prevalence of depression in patients with T2DM in Korea has been reported as high as 22.6% to 28.8% [ 18 19 ]. In the analysis using the NHIS DB, depression in T2DM was defined as both T2DM and depression (ICD-10 code of F320-349) with at least one prescription for antidepressants ( Table 1 ) [ 20 ].…”
Section: Depression In T2dmmentioning
confidence: 99%
“…According to the analysis of the NHIS DB from 2003 to 2013, the annual prevalence rates of depression consistently increased both in T2DM and the general population without T2DM ( Fig. 4 ) [ 20 ]. During the study period, the prevalence rate of depression in T2DM was about two-fold higher compared to the general population (9.6% vs. 4.6% in 2013).…”
Section: Depression In T2dmmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with T2DM often have comorbid depression, and up to 27.6% of patients with T2DM have suffered from clinically relevant depressive symptoms (Lloyd et al, 2018). Comorbid depression may worsen health outcomes, such as poor self-management (Schmitt et al, 2017), worse glycemic control (Alzughbi et al, 2020), a lower quality of life (Patra et al, 2020), and a higher risk of mortality (Jeong et al, 2017). Exploring the causes and mechanisms of depression in patients with T2DM may provide a new avenue for identifying the risk factors and for formulating targeted interventions to prevent the onset or delay the progression of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Jeong et al [ 9 ] retrospectively showed that the annual prevalence of depression was higher in T2DM and higher morality was shown in the depressed subjects from the nationwide health insurance service database in Korea. It was the first longitudinal data from Koreans, and the findings are consistent with the previous results that patients with depressed symptoms showed increased mortality in patients with diabetes mellitus.…”
mentioning
confidence: 99%